Optimum Selection of Communication Tower Structures Based on Wind Loads & lifecycle cost analysis. Issue 1 (31st December 2022) - Elhakim, Yasmin; Ismail, Tawfik; Fahim, Irene
Abstract: Communication towers are vital assets in our daily lives as they transfer signals between cell phones facilitating communication and commerce among people and businesses all around the world. Wind loads are crucial in the communication towers design since they are tall and slender. With climate change bringing more storms and higher wind speeds, it is more crucial to research the finest tower structure that withstands such conditions with the least life cycle cost. Therefore, in this paper, a comparative case study is performed between 45 m height lattice tower and monopole tower in Egypt. Two locations were considered, the first is inside the city and the second is an open terrain. In addition, two load scenarios were investigated. The comparison parameters are the behavior under critical wind loads taking into account three wind speeds which are 100 km/hr, 130 km/hr and 140 km/hr, and life cycle cost analysis. It was found that the lattice tower behaves better under critical wind loads with a maximum tilting equal to 0.4784 degrees at location 1, load 2, and a wind speed of 140 km/hr compared to 0.5806 in the case of the monopole tower. Similarly, the lattice tower behaves better at the second location as well. However, the monopole tower has less life cycle cost with a total life cycle cost of 3, 201, 846.80 EGP compared to 4, 380, 419.91EGP in case of lattice tower. Therefore, based on the location, wind speed, and available land area, and life cycle cost assessment, the optimum tower structure could be selected.